Wave scattering of plane wave at the loosely bonded interface of two dissimilar rotating triclinic magneto-thermoelastic media under nonlinear thermoelasticity and DPL model. Issue 11 (21st September 2022) - Karmakar, Subhashis; Sahu, Sanjeev A.; Goyal, Suman
Abstract: In the present work, the reflection and transmission of plane waves incident at the loosely bonded interface between two dissimilar anisotropic (triclinic), rotating magneto-thermoelastic media is studied. Four non-linear theories of thermoelasticity namely Classical coupled theory (CL), Lord-Shulman theory (LS), dual-phase-lag (DPL) model and Green-Naghdi theory (GNIII) are employed. Using these theories, the effect of mechanical and thermal bonding parameters on the reflection and refraction coefficients is compared. Moreover, the effect of magnetic field and angular velocity on the reflection and refraction coefficients is discussed with the help of graphs under different thermoelastic theories. Energy partition of reflected and transmitted waves are also carried out which validates the problem.